1985
DOI: 10.1016/0014-5793(85)80229-5
|View full text |Cite
|
Sign up to set email alerts
|

The amino acid sequence of hemoglobin I from Parasponia andersonii, a nonleguminous plant

Abstract: The complete ammo acid sequence of the hemoglobm I from nitrogen-fixing root nodules of the nonlegummous plant, Paraspomu andersonu, has been determined This dimeric protein consists of two ldentlcal polypepttde chains of 155 ammo acids and shows extensive sequence homology with other hemoglobms Homology between the hemoglobm I of P andersomz and the leghemoglobms of lupm and soybean nodules IS 41 and 39%, respectively The predicted secondary structure of P andersonu hemoglobm I has a high content of a-hehx, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0

Year Published

1986
1986
1992
1992

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 15 publications
2
16
0
Order By: Relevance
“…PA2a and PA2b were cleaved with cyanogen bromide (CNBr) (12) and the resulting fragments were fractionated by reversed-phase HPLC on a Waters /zBondapak C18 column using an acetonitrile gradient. The isolated CNBr peptides were digested with trypsin (Worthington), chymotrypsin (Worthington) or Staphylococcus aureus V8 protease (Pierce) and the resultant peptides isolated by reversed-phase HPLC as described by Kortt et al (17). All peptides were sequenced manually by a modified Edman procedure (21) using 50o7o pyridine as the coupling buffer and extracting with nheptane-ethyl acetate (2 : 1, v/v) instead of benzene.…”
Section: Amino Acid Sequencingmentioning
confidence: 99%
“…PA2a and PA2b were cleaved with cyanogen bromide (CNBr) (12) and the resulting fragments were fractionated by reversed-phase HPLC on a Waters /zBondapak C18 column using an acetonitrile gradient. The isolated CNBr peptides were digested with trypsin (Worthington), chymotrypsin (Worthington) or Staphylococcus aureus V8 protease (Pierce) and the resultant peptides isolated by reversed-phase HPLC as described by Kortt et al (17). All peptides were sequenced manually by a modified Edman procedure (21) using 50o7o pyridine as the coupling buffer and extracting with nheptane-ethyl acetate (2 : 1, v/v) instead of benzene.…”
Section: Amino Acid Sequencingmentioning
confidence: 99%
“…A chymotryptic peptide with a blocked N terminus and composition of Asp, Ser(3), Glu, Val, Lys, Phe was also isolated. The sequence of the blocked tryptic peptide T1, can be deduced from its composition and the sequence of S. aureus protease peptide S1 [8], as S-S-S-E-V-N-K, consistent with the sequence of the N-terminal tryptic peptide in the DNAderived sequence. These results confirm that the N terminus of hemoglobin I contains the additional four residues observed in the DNA sequence and that the N-terminal serine is 10 20…”
Section: Re-examination Of P Andersonii Hemoglobin I Sequencementioning
confidence: 65%
“…A re-examination of the peptide data [8] revealed that Phe36 was missed in the original sequence because of the single-residue overlap provided by the peptic peptide overlapping Phe35 of T4 and Leu37 of C6, which failed to account for the extra Phe in the sequence Phe35-Phe-Leu37. The valine at 73 was missed owing to an error in collating the original sequence data.…”
Section: Re-examination Of P Andersonii Hemoglobin I Sequencementioning
confidence: 99%
See 2 more Smart Citations